Building Autonomous Learners Perspectives from Research and Practice using Self-Determination Theory - Liu, Woon Chia; Wang, John Chee Keng; Ryan, Richard M. (Springer Nature Singapore : Imprint: Springer, 2016)
This edited work presents a collection of papers on motivation research in education around the globe. Pursuing a uniquely international approach, it also features selected research studies conducted in Singapore under the auspices of the Motivation in Educational Research Lab, National Institute of Education, Singapore. A total of 15 chapters include some of the latest findings on theory and practical applications alike, prepared by internationally respected researchers in the field of motivation research in education. Each author provides his/her perspective and practical strategies on how to maximize motivation in the classroom. Individual chapters focus on theoretical and practical considerations, parental involvement, teachers' motivation, ways to create a self-motivating classroom, use of ICT, and nurturing a passion for learning. The book will appeal to several different audiences: firstly, policymakers in education, school leaders and teachers will find it a valuable resource. Secondly, it offers a helpful guide for researchers and teacher educators in pre-service and postgraduate teacher education programmes. And thirdly, parents who want to help their children pursue lifelong learning will benefit from reading this book.